Fodder potential of triticale (× Tritisecale Wittmack) genotypes in Nepal: Evaluation of biomass and seed productivity - Ghimire, Ram Prasad; Russell, Adrian; Pariyar, Dinesh; Hampton, John; Armstrong, Keith; Shrestha, Kishor Kumar; Rolston, M. Phil; Stevens, E John; Amgain, Rita (Nepal Agriculture Research Journal, 2025)
Triticale (× Triticosecale Wittmack) is a hybrid cereal combining the high grain quality and yield potential of wheat with the adaptability and resilience of rye. This study evaluates the performance of three triticale cultivars (Bolt, Wintermax and Crackerjack) and recommended cultivars of wheat and oat for winter fodder and seed production across four ecological regions in Nepal. A randomized complete block design (RCBD) with three replications was used to assess fodder yield and quality, and seed production over two consecutive years. Fodder yield varied significantly (p<0.001) among cultivars and locations, with Oat-RC demonstrating the highest biomass production, followed by TC-Wintermax, which outperformed TC-Bolt and TC-Crackerjack. The crude protein content ranged between 9.09% and 9.87%, with TC-Crackerjack exhibiting the best on fiber composition analysis. Seed yield was significantly influenced by genotype and environment, with TC-Bolt achieving the highest yield, particularly at Dhunche and Khumaltar, while TC-Wintermax demonstrated stable performance across sites. The study highlights the adaptability of triticale to Nepal’s diverse agro-ecological conditions and its potential as a sustainable alternative for winter fodder and grain production. The findings provide the valuable insights for optimizing region-specific cultivar recommendations to enhance livestock nutrition and agricultural sustainability.